Perceived vulnerability in consumer ethnocentrism - Wise Lozano, Jorge Alberto (My University, 2017)
This research establishes that the consumer’s perceived vulnerability to a threat is a relevant variable that modifies the preference for domestic origin products. Many times, consumers balance their personal well-being with their sense of in-group identity, particularly when their preference for domestic products above foreign ones is expected. This study demonstrates that perceived vulnerability to a threat such as damaging one’s personal well-being is a relevant factor when consumers express their preference for domestic products.
International Journal of business and social research
Keywords: Consumer ethnocentrism; Consumer preference; Domestic products; Mexico; Perceived vulnerability